Measurement of b-hadron masses* - Aaij, Roel; Bachmann, Sebastian; Bien, Alexander; Britsch, Markward; Blouw, Johan; Dordei, Francesca; Eisele, Franz; Färber, Christian; Hansmann-Menzemer, Stephanie; Hartmann, Tobias; Jäger, Andreas; Kreplin, Katharina; et al. (Physics letters, 2012)
Measurements of b-hadron masses are performed with the exclusive decay modes B+→J/ψK+, B0→J/ψK⁎0, B0→J/ψKS0, Bs0→J/ψϕ and Λb0→J/ψΛ using an integrated luminosity of 35 pb−1 collected in pp collisions at a centre-of-mass energy of 7 TeV by the LHCb experiment. The momentum scale is calibrated with J/ψ→μ+μ− decays and verified to be known to a relative precision of 2 ×10−4 using other two-body decays. The results are more precise than previous measurements, particularly in the case of the Bs0 and Λb0 masses.
LHCb Collaboration: R. Aaij, S. Bachmann, A. Bien, J. Blouw, M. Britsch, F. Dordei, F. Eisele, C. Fäber, S. Hansmann-Menzemer, T. Hartmann, A. Jaeger, K. Kreplin, G. Krocker, P. Krokovny, C. Langenbruch, C. Linn, J. Marks, M. Meissner, P. Seyfert, S. Stahl, J. v. Tilburg, U. Uwer, S. Wandernoth, D. Wiedner, A. Zhelezov [und weitere]
Gesehen am 31.10.2018